Fifteen-minute consultation: Child with an incidental finding of a fatty liver. Issue 4 (14th May 2021) - Chan, Joseph; Gupte, Girish
Abstract : The incidental finding of a fatty liver on an abdominal ultrasound scan performed for an unrelated reason in an overweight child is an increasingly common phenomenon in paediatric practice. This article will explain the steps to be taken when receiving such an ultrasound report.